The COVID-19 Pandemic and Human Rights Limitation: The Role of Trust and Communication in Vietnam - Vu, Van Thanh (ASIAN REVIEW, 2021)
The COVID-19 pandemic is an unprecedented health crisis in modern history, causing disruption and chaos to the usual way of life, and requiring radical measures. This study investigates how willingly Vietnamese people cooperate with their government’s anti-pandemic measures, which limit their right to assembly, privacy and freedom of movement during the COVID-19 pandemic. The findings show that the region of residence of the respondents influences their cooperation with government’s measures. It has also been found that the more the respondents have trust in the government as an important agency in pandemic management, the more they cooperate with the government’s measures.